Cresyl violet staining to assess neuroprotective and euroregenerative effects of Haruan traditional extract against eurodegenerative damage of ketamine - Mohd Shafri, Mohd Affendi; Mat Jais, Abdul Manan; Md. Jaffri, Juliana; Min, Kyu Kim; Ithnin, Hairuszah; Mohamed, Farahidah (Academic Sciences, 2012)
Ketamine abuse is on the increase in Malaysia. Neurodegenerative change following ketamine use results in debilitating behavioural and cognitive dysfunctions. These changes are thought to be the consequences of network and cellular disorganization and degeneration in the brain involving areas such as hippocampus. Ketamine works by blocking NMDA receptor and hence ketamine research has value in study on NMDA-related neurological disorders such as schizophrenia. This work study the histological change in rats brain which was exposed to ketamine and the effect of treating ketamine-exposed rats with haruan traditional extract (HTE) a substance which has been shown to have positive neuroregenerative function in cell culture study. The changes were studied using cresyl violet and parameters such as pathological score, dead cell count and degenerative change were evaluated. It was demonstrated that ketamine influences these parameters in exposure length-dependent manners and degenerative change could be ameliorated by supplementation with haruan therapeutic extract (HTE) pre-damage induction but not post-damage induction. The result adds to the growing number of evidence on neuroplasticity, and the possible role of non-endogenous substances in protecting as well as inducing genesis of neurons for diseases that share similar pattern of neurological change as ketamine-abused subjects.